Determinan Perilaku Hedonic Shoping Di Era Digital - Djuharni, Darti; Dini, Maisa; Liana, Yuyuk; Lutfillah, Novrida Qudsi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : to uncover and examine the factors that drive hedonic shopping behavior that leads to impulse buying Design/Methode/Approach : The research was conducted by distributing questionnaires to respondents in Java and Kalimantan in the form of google form (online). The number of samples is based on the number of indicators multiplied by 5, so that the number of 155 respondents is obtained which then the results of their answers are processed using PLS. The variables used in this research are website quality, hedonic shopping motivation, and sales promotion as independent variables, and impulse buying as the dependent variable. Research Finding : hedonic shopping incentive has a favorable and significant impact on impulsive purchasing whereas website quality has no bearing on this behavior. Sales promotions have a similar beneficial and strong impact on impulsive purchases. Additionally, it has been demonstrated that sales promotions make the link between website quality and impulsive purchases stronger. Theoretical contribution/Originality : The results of this study can add references for the development of marketing materials, especially those related to customer behavior. Practitionel/Policy implication : The results of this study can be input for companies and entrepreneurs to better understand consumer buying behavior and the factors that trigger impulse purchases so as to increase sales. Research limitation : This research is limited to three independent variables, namely website quality, hedonic shopping motivation, and sales promotion which influence impulsive purchases.